Introduction to Geriatric Rehabilitation - (:unkn) unknown (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2009)
Comprehensive geriatric assessment and rehabilitation is based on interdisciplinary team-work with a functional-orientated approach. Medical doctors, rehabilitation nurses, physiotherapists, occupational therapists, speech therapists and social workers make the team in geriatric rehabilitation. Hospital-based, home-based or outpatient rehabilitation programs should be provided to the elderly patients if needed. The complexity of physical, psycho-social and medical comorbidities usually becomes the focus of hospitalization and requires intensive medical treatments. The health status of the elderly patient should be maintained in his or her optimal conditions for success of the rehabilitation. Primary and secondary prevention is essential, and physical, psychosocial and environmental factors that impact on the well-being of older individuals should be evaluated by comprehensive geriatric assessment. Using an organized approach with objective measurements provides information about the factors that can deteriorate the functional status. The important areas which need to be evaluated are: activities of daily living, cognition, mood, social supports, gait and falls, nutrition, sensory impairments, incontinence, polypharmacy, elder abuse, pressure sores and pain. Turk J Phys Med Rehab 2009; 55 Suppl 2:80-4.
Keywords: Rehabilitation team; institutional rehabilitation; non-institutional rehabilitation; physical assessment of a geriatric patient; laboratory findings of a geriatric patient; multiple aspects of geriatric evaluation; interdisciplinary approach; MANAGEMENT; PAIN